Potassium conductance increased by noradrenaline, opioids, somatostatin, and G-proteins: whole-cell recording from guinea pig submucous neurons - Tatsumi, H (J Neurosci, 1990)
Agonists at alpha 2-adrenoceptors, delta-opioid receptors, and somatostatin receptors were applied to dissociated guinea pig submucous plexus neurons; whole-cell recordings of membrane current showed that they increased the membrane potassium conductance. The conductance affected showed inward rectification, being described by Gag(max)/[1 + exp((V - V0.5)/k)] where V0.5 was about -65 mV and Gag(max) was about 10 nS. The agonists were ineffective when the potassium conductance of the neurons had first been increased by intracellular dialysis with purified guanosine 5-triphosphate (GTP)-binding proteins (Gi or Go). Agonist actions were prevented by pertussis toxin, applied intracellularly (10–100 ng/ml for several minutes) or extracellularly 1– 10 micrograms/ml for 1 hr); in the latter case, the agonist responses were reconstituted by intracellular dialysis with GTP-binding proteins.